Analysis of Factors Affecting Coverage Immunization Hepatitis B in the Regionwork Panga Health Center Aceh Jaya District - Cut Nazimah; Ismail Efendy; Nur Aini (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Immunization coverage in the Panga Publich Health Center only reaches 40.56%. This study aims to identify and analyze the factors that influence the low coverage of Hepatitis B immunization. This research was a mix method research design explanatory research. The study was conducted at Panga Publich Health Center, Aceh Jaya Regency from July to August 2022. The number of samples was 66 mothers who had toddlers obtained by purposive sampling. The number of informants is 11 people. Analysis of quantitative data was carried out by using univariate analysis test, bivariate analysis using Chi-square test and multivariate using logistic regression test. Qualitative data analysis using interactive analysis. The results of the quantitative research show that in the univariate analysis of 66 respondents, most of them aged 36-45 years (56.1%), high school education, (53.0%), having a job as self-employed (37.9%). The results of the bivariate analysis showed that knowledge, attitudes, beliefs, facilities, husband's support, support of health workers affected by the coverage of Hepatitis B immunization in the Panga public Health Center Work Area Aceh Jaya Regency. The results of the multivariate analysis showed that the variable that had the most influence on the coverage of Hepatitis B immunization was the trust variable. The results of the qualitative analysis showed that most of the children in the Panga public Health Center Work AreaAceh Jaya Regency was not immunized against hepatitis B, the community believed that the raw material for hepatitis B immunization was not halal. Based on the results of this study, it was recommended that the results of this study be used as reading material and evidence based for students who are working on college assignments and final projects, especially those related to factors that affect immunization coverage.Keywords: Factors, Hepatitis B, Immunization Coverage